El atardecer de la modernización: La historia del megaproyecto hídrico GUATAPÉ- PEÑOL en el noroccidente colombiano, años 1960/1970 (2020)
The Antioquia’s history, in economics mainly, has been treated as a whole, even on very precise grounds as: minig, industry and commerce. Although the political and sociocultural impact that the new hydroelectric power stations have had since the ending of twentieth century, the one that need to be told is the socioelectrical history, specially the Guatapé Peñol project, whith the final sinking of two towns and a large amount of land useful for peasants. A glimpse to this project, that regains the voice of those towns is the purpose of this paper.